2019
DOI: 10.1002/ijc.32067
|View full text |Cite
|
Sign up to set email alerts
|

Psychological effect of cervical cancer screening when changing primary screening method from cytology to high‐risk human papilloma virus testing

Abstract: From 2015, Norway has implemented high‐risk human papilloma virus (hrHPV) testing in primary screening for cervical cancer. Women aged 34–69 years, living in four counties, have been pseudo‐randomly assigned (1:1 randomization) to either hrHPV testing every 5 years (followed by cytology if hrHPV is positive), or cytology testing every 3 years (followed by hrHPV testing if low‐grade cytology is detected). We compared anxiety and depression scores among participants by screening arm and results. In total, 1,008 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Reassuringly, women with persistent HPV and normal cytology at 12 months did not have significantly higher anxiety than the control group, although descriptively they displayed slightly higher anxiety than would be expected in the general population (mean score of 36.8 compared to normal range of 34–36). This suggests that raised levels of anxiety and distress associated with an initial HPV positive result may normalise with repeated exposure to the result and/or over time, which is consistent with previous research . Our findings suggest that efforts to reduce anxiety should therefore primarily focus on women who test HPV positive with normal cytology for the first time.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Reassuringly, women with persistent HPV and normal cytology at 12 months did not have significantly higher anxiety than the control group, although descriptively they displayed slightly higher anxiety than would be expected in the general population (mean score of 36.8 compared to normal range of 34–36). This suggests that raised levels of anxiety and distress associated with an initial HPV positive result may normalise with repeated exposure to the result and/or over time, which is consistent with previous research . Our findings suggest that efforts to reduce anxiety should therefore primarily focus on women who test HPV positive with normal cytology for the first time.…”
Section: Discussionmentioning
confidence: 55%
“…At the population level, it is unlikely that the levels of anxiety observed in our study would cause significant disruptions to women's daily functioning. This is supported by our small between‐group differences for general distress paired with wider evidence indicating that screening‐related anxiety is usually temporary . However, it is important to remember that 72% of women aged 25–64 living in the UK attend for screening when invited, of whom 8.5% are likely to be HPV positive with normal cytology .…”
Section: Discussionmentioning
confidence: 68%
“…Seventeen papers were quantitative studies (Alay et al, 2019;Andreassen et al, 2019;Ferenidou et al, 2012;Garces-Palacio et al, 2019;Hsu et al, 2018;Kitchener et al, 2008;Kwan et al, 2011;Maggino et al, 2007;Maissi et al, 2004Maissi et al, , 2005McBride et al, 2020;McCaffery et al, 2004;Nagele et al, 2019;Ngu et al, 2018;Rodriguez et al, 2019;Wang et al, 2010;Wang et al, 2011), 15 were qualitative (Barrera-Clavijo et al, 2015;Barreto et al, 2016;Bertram & Magnussen, 2008;Head et al, 2017;Kosenko et al, 2012;Lin et al, 2011;Linde et al, 2019;McCaffery & Irwig, 2005;McCaffery et al, 2006;McCurdy et al, 2011;O'Connor et al, 2014;Perrin et al, 2006;Tiro et al (2019); Waller, McCaffery, et al, 2007;Wyndham-West et al, 2018) and one was mixed-methods (Daley et al, 2010). A total of 12,789 women aged between 18 and 65 participated in twenty studies (n=12,244 quantitative; n=545 qualitative), of whom 4,305 were reported as having tested positive for HPV (n=3,874 quantitative; n=431 qualitative).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…See Figure 3(a)-(c) for the meta-analysis findings and papers included. Four studies which measured anxiety could not be meta-analysed due to study design (e.g., no suitable control group; (Ngu et al, 2018)) or lack of published data in the necessary format for extraction (Alay et al, 2019;Andreassen et al, 2019;Maggino et al, 2007). Consistent with the meta-analysis findings, two of these studies reported higher short-term anxiety in HPV-positive groups compared to controls (Alay et al, 2019;Maggino et al, 2007) but not long-term anxiety (Andreassen et al, 2019); and one study without a suitable control group found that anxiety decreased over time (Ngu et al, 2018).…”
Section: Mccaffery and Irwig (2005)mentioning
confidence: 99%
See 1 more Smart Citation